Impact of the off-balance sheet on capital adequacy Application study in National Bank of Iraq For the period(2017 – 2008) - Ahmed Youcef, Rawaa (Finance and Business Economies Review, 2019)
The research to determine the effect of off-balance sheet on capital adequacy, as one fields investing money in banks, where this point become one of the topics that have been interesting recently. Due to the developments in the fields of trade and contracting which bank consider as one of their parts. National Bank of Iraq have been chosen to achievement the goal of this study. This study concluded that there are the significant impact between off balance sheet and capital adequacy , Thus The alternative hypothesis has been proved which included ( There are significant impact between off balance sheet and capital adequacy ) by using simple linear regression . The study recommended that there should be rules and regulations governing the use of funds in off balance sheet in order to avoid future risk to the bank.